SISTEM PENDUKUNG KEPUTUSAN PENENTU RUMAH SEHAT MENGGUNAKAN METODE SAW (Simple Additive Weighting) (Information Technology and Telematics, 2015)
Abstract -- Home or place of residence is a primary need for every human being. The house serves as a place to unwind after a day of work or activity, a place to hang out and foster a sense of kinship. nearly half of human life will be at home, so the house will have a major impact on the health condition of the residents. To improve the health of neighborhood health center in the village stranding create a healthy home assessment with appropriate indicators or parameters Kepmenkes No. 829 / Menkes / SK / VII / 1999, but a healthy home assessment conducted Posyandu not computerized and still use manual calculation. then made a decision support system determinants of healthy home using SAW (Simple Additive Weighting). Keywords -- Healthy home, Decision support system, SAW(simple additive weighting) method. I  PENDAHULUAN